EXPLORING THE IMPACT OF NURSING TECHNICIANS AND HEALTH ASSISTANTS ON PATIENT CARE IN HAFAR AL-BATIN HOSPITALS: A MIXED-METHODS STUDY - Abdullah Lafi Mohammed Almutairi, Fawaz Saqr Matar Almutairi, Ahmed Munif Saud Al-Shammari, Abdalrahmin Muhamad Almutairi, Eman Hamed Hindi Aldhferi, Ahoud Gharbi Aldhafeeri, Mohammed saud abdullah aljameeli, Fooz Abdullah Muteliq Al-Jumaili (Chelonian Research Foundation, 2022)
This mixed-methods study investigates the impact of nursing technicians and health assistants on patient care in hospitals located in Hafar Al-Batin, Saudi Arabia. The study employs a convergent parallel design, combining quantitative surveys and qualitative interviews to gather data from nursing technicians, health assistants, and staff nurses. The quantitative data were analyzed using descriptive and inferential statistics, while the qualitative data were analyzed using thematic analysis. The findings reveal that nursing technicians and health assistants play crucial roles in patient care, including direct patient care, medication administration, and assisting with medical procedures. However, challenges such as heavy workloads, limited training opportunities, and role ambiguity were identified. The study highlights the need for enhanced training programs, clear role definitions, and improved collaboration among healthcare professionals to optimize patient care. The integration of quantitative and qualitative findings provides a comprehensive understanding of the impact of nursing technicians and health assistants on patient care in Hafar Al-Batin hospitals. This study contributes to the limited research on this topic in Saudi Arabia and offers recommendations for healthcare administrators and policymakers to enhance the utilization of these essential healthcare professionals.